2012
DOI: 10.1371/journal.pone.0038220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Characterization of a Patient Carrying a Compound Heterozygous Pericentrin Mutation and a Heterozygous IGF1 Receptor Mutation

Abstract: Intrauterine and postnatal longitudinal growth is controlled by a strong genetic component that regulates a complex network of endocrine factors integrating them with cellular proliferation, differentiation and apoptotic processes in target tissues, particularly the growth centers of the long bones. Here we report on a patient born small for gestational age (SGA) with severe, proportionate postnatal growth retardation, discreet signs of skeletal dysplasia, microcephaly and moyamoya disease. Initial genetic eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In this review, leukocytosis and/or thrombocytosis was not mentioned as a finding . Our search of the literature showed that no study provided the leukocyte or platelet counts in patients with MOPD II , except for the above mentioned two case reports and Case 6 in the present study, which had been previously published in relation to moyamoya and recurrent strokes .…”
Section: Discussionmentioning
confidence: 60%
“…In this review, leukocytosis and/or thrombocytosis was not mentioned as a finding . Our search of the literature showed that no study provided the leukocyte or platelet counts in patients with MOPD II , except for the above mentioned two case reports and Case 6 in the present study, which had been previously published in relation to moyamoya and recurrent strokes .…”
Section: Discussionmentioning
confidence: 60%
“…Digenic or oligogenic inheritance patterns in the context of growth deficits have been recently suggested in a patient with IGF-1 deficiency due to a combined STAT5B and IGFALS mutation, although definite final evidence for the pathogenicity of either variant is lacking [40,41]. In contrast, the phenotype of a girl with a combined pericentrin ( PCNT ) and IGF1R mutation was shown to be merely attributable to the compound pericentrin mutations [42], emphasizing the need for thorough genetic and molecular evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were sent to the Laboratory for Diagnostic Genome Analysis, Department of Clinical Genetics at the Leiden University Medical Center (LUMC) for routine genetic testing of IGF1R . Targeted Sanger sequencing of the complete coding region exon 1-21 including intron/exon boundaries (NM_000875.3) was performed as previously reported (10,16). Multiplex ligation-dependent probe amplification (MLPA) assay (MRC Holland kit P217-B2) containing probes for IGF1R exon 1-21 was performed for the detection of deletions or duplications (16).…”
Section: Methodsmentioning
confidence: 99%